Structure of Gα(i1) bound to a GDP-selective peptide provides insight into guanine nucleotide exchange - Johnston, Christopher A. (2005)
Heterotrimeric G-proteins are molecular switches that regulate numerous signaling pathways involved in cellular physiology. This characteristic is achieved by the adoption of two principal states: an inactive, GDP-bound and an active, GTP-bound state. Under basal conditions G-proteins exist in the inactive GDP-bound state, thus nucleotide exchange is crucial to the onset of signaling. Despite our understanding of G-protein signaling pathways, the mechanism of nucleotide exchange remains elusive. We employed phage display technology to identify nucleotide-state-dependent Gα binding peptides. Herein, we report a GDP-selective Gα-binding peptide, KB-752, that enhances spontaneous nucleotide exchange of Gα(i) subunits. Structural determination of the Gα(i1)/peptide complex reveals unique changes in the Gα switch regions predicted to enhance nucleotide exchange by creating a GDP dissociation route. Our results cast light onto a potential mechanism by which Gα subunits adopt a conformation suitable for nucleotide exchange.